(untitled) (International Journal of Engineering and Computer Science, 2017)
: Due to the existence of cloud computing , owners of that particular data had determined to push their complex data systems from local database systems to the public cloud which is commercial for better flexibility and for economical preservation. In order to protect privacy of data, the data that is sensitive need to be encrypted before deploying the data onto the cloud, however, it is very different from the plaintext keyword match which is a old-fashioned technique. Therefore, the searching of data on encrypted data is the prime importance. There are many data users who wish to search a file, based on their desired keywords, the file must be extracted matching the relevance of that user entered keywords. In this paper, we are designing and solving the provocation problem of securing Privacy over Encrypted cloud-data using Multiple keywords Rank based Search (PEMRS). We initiate a set of strong privacy essentials for a secure cloud-data using system.